Assessing the Effectiveness of Academic Integrity Institutional Policies: How Can Honor Code and Severe Punishments Deter Students’ Cheating—Moderating Approach? - Jovana Janinovic; Sanja Pekovic; Rajka Djokovic; Dijana Vuckovic (SAGE Open)
This paper examined the role of honor codes and severity of punishment on the students’ perception of cheating seriousness in order to assess the effectiveness of institutional policies on preventing the academic misconduct. In order to further put into perspective the obtained results, two moderating factors were included in the empirical analysis—students’ understanding and support of cheating policies. Empirical analysis of our survey including 486 students of University of Montenegro revealed that honor code has positive but mild effect on students’ perception of cheating seriousness while severity of punishment has no impact at all. In addition, understanding university’s cheating policies moderates positively the effect of both honor code and severity of punishment on cheating deterrence. Support of university’s cheating policies was found to amplify the positive relation between honor code and perceived cheating seriousness, but does not moderate the correlation between severity of punishment and students’ perceived cheating seriousness. Our results indicate that policy makers in the field should strive to enhance impact of honor codes and sanctions by consistently acknowledging, communicating, and involving students in design and implementation of institutional integrity policies.